Massive star formation in the infrared dark cloud G024.64+00.16 - Ulberstad, Emma; Lind, Axel; Askbom, Ludvig (My University, 2020)
Massive stars drive the energy content and chemical enrichment of galaxies. Despite their importance, it is still not fully understood what mechanisms leads to the formation of massive stars. It is therefore important to study the regions in the universe where massive stars form, infrared dark clouds, to better understand the physical conditions under which massive star formation occurs. In this project we have investigated the kinematic structure, physical conditions and star formation content of the IRDC G024.64+00.16. We have used a mass surface density map obtained from near IR data to investigate the presence of massive cores within the cloud. Multi wavelength images obtained by Spitzer and Hershel have been used to identify the relative evolutionary stage of these massive cores. We have also used 13CO(1-0) and C18O(1-0) maps from the FUGIN survey to investigate the kinematics of the gas at the cloud and core scale. The physical conditions of the cores were determined by calculating the column density, the mass surface density and the depletion for 13CO and C18O. A virial analysis was done to estimate if the gas of the cores are gravitationally bound or unbound. We nd that the IRDC contains three cores and that none of these are associated with IR signatures at 4.5, 8, 24 or 70 μm, indicating that these cores are likely at an early relative evolutionary stage. Finally, we nd that the cores within the cloud show 13CO and C18O column densities in the range 1.87 - 2.28 1016 cm􀀀2 and 0.50 - 0.81 1016 cm􀀀2 respectively, virial parameters vir >1 and depletion factors in the range 6.15 - 10.13 for 13CO and 2.80 - 6.41 for C18O.
Keywords: Massive star formation, infrared dark cloud, G024.64+00.16